Spatial extent of a Landauer residual-resistivity dipole in graphene quantified by scanning tunnelling potentiometry - Willke, Philip; Druga, Thomas; Ulbrich, Rainer G.; Schneider, M. Alexander; Wenderoth, Martin (Nature Communications, 2015)
Electronic transport on a macroscopic scale is described by spatially averaged electric fields and scattering processes summarized in a reduced electron mobility. That this does not capture electronic transport on the atomic scale was realized by Landauer long ago. Local and non-local scattering processes need to be considered separately, the former leading to a voltage drop localized at a defect, the so-called Landauer residual-resistivity dipole. Lacking precise experimental data on the atomic scale, the spatial extent of the voltage drop remained an open question. Here, we provide an experimental study showing that the voltage drop at a monolayer-bilayer boundary in graphene clearly extends spatially up to a few nanometres into the bilayer and hence is not located strictly at the structural defect. Moreover, different scattering mechanisms can be disentangled. The matching of wave functions at either side of the junction is identified as the dominant process, a situation similar to that encountered when a molecule bridges two contacts.